2022
DOI: 10.53424/balikesirsbd.1075926
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the COVID-19 Pandemia on the Use of Cancer Early Diagnosis Screening and Training Centers Services

Abstract: Amaç: Bu çalışma COVID-19 pandemisinin Kanser Erken Teşhis, Tarama ve Eğitim Merkezleri (KETEM) hizmetlerinin kullanımı üzerindeki etkisini değerlendirmek amacıyla yapılmıştır. Gereç ve Yöntem: Retrospektif kohort tipinde betimleyici olarak yürütülen bu araştırmada, 2017-2020 yıllarında 1 Ocak-31 Aralık tarihleri ile 1 Ocak-1 Ekim 2021 tarihleri arasında bir ilin Kanser Erken Teşhis, Tarama ve Eğitim Merkezleri’ne yapılan toplam 52.955 hasta başvuru kaydı incelenmiştir. Çalışma kapsamında elde edilen veriler f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In this study, it was found that only one out of every five women undergoes regular pap smear screening. Comparatively, before the pandemic in developing countries, this rate stood at 27.2% in Malaysia [30], 28.2% in Turkey [28], and 32% in Iran [31]. In contrast, developed countries exhibited significantly higher rates, with 70% of women in Finland [31], 89.1% in the USA [32], 83% in the UK [33], and a striking 94% in Greece [34] having undergone pap smear tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, it was found that only one out of every five women undergoes regular pap smear screening. Comparatively, before the pandemic in developing countries, this rate stood at 27.2% in Malaysia [30], 28.2% in Turkey [28], and 32% in Iran [31]. In contrast, developed countries exhibited significantly higher rates, with 70% of women in Finland [31], 89.1% in the USA [32], 83% in the UK [33], and a striking 94% in Greece [34] having undergone pap smear tests.…”
Section: Discussionmentioning
confidence: 99%
“…This finding underscores the positive aspect that individuals who undergo CBE are more likely to be recommended for mammography as a follow-up assessment. Similarly, individuals participating in one screening program tend to participate in others as well Research has indicated that women who undergo pap smear tests exhibit a heightened awareness of breast cancer [28]. Nonetheless, it is worth noting that these rates fall significantly below the national mammography target, given that the goal for community-based mammography screening in Turkey is presumed to be 70% [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation